2011
DOI: 10.1084/jem.20100508
|View full text |Cite
|
Sign up to set email alerts
|

MHCII glycosylation modulates Bacteroides fragilis carbohydrate antigen presentation

Abstract: N-linked glycans on class II MHC molecules are required for the presentation of glycoantigens, but not peptide antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 45 publications
(119 reference statements)
1
68
0
Order By: Relevance
“…Upon neutralization of either charge, the antigen is rendered inactive (6,11,12) due in part to conformational changes that result in loss of MHCII binding (12). Interestingly, we have also found that the glycosylation pattern on MHCII directly impacts MHCII binding by PSA, likely through carbohydrate-carbohydrate interactions with conserved N-linked glycans on MHCII (13)(14)(15). Despite these advances in our understanding of MHCII-mediated presentation of these unusual antigens, almost nothing is known about their recognition by their cognate T cell.…”
mentioning
confidence: 64%
“…Upon neutralization of either charge, the antigen is rendered inactive (6,11,12) due in part to conformational changes that result in loss of MHCII binding (12). Interestingly, we have also found that the glycosylation pattern on MHCII directly impacts MHCII binding by PSA, likely through carbohydrate-carbohydrate interactions with conserved N-linked glycans on MHCII (13)(14)(15). Despite these advances in our understanding of MHCII-mediated presentation of these unusual antigens, almost nothing is known about their recognition by their cognate T cell.…”
mentioning
confidence: 64%
“…S3). The N-glycans on class II are thought to play a role in proper folding of nascent molecules (31), in protease resistance (32), in facilitating optimal receptor geometry for APC/T-cell communication (33), and, most recently, in presentation of particular carbohydrate antigens (34). We found that the α1 domain N-glycan at szDOvαN79, near α-chain/β-chain interface and homologous to αN78 in conventional MHC class II, influences the aggregation state of the molecule (Fig.…”
Section: Effect Of Mutations In the Dmβ2 Domain On Interaction With Domentioning
confidence: 99%
“…Asparagine-linked glycosylation is one of the most common post-translational modifications of eukaryotic proteins (14). In general, the role of N-linked glycosylation in folding, secretion, and resistance to proteolysis is understood for several proteins (15,16), and several examples have exemplified the crucial role of N-glycans in protein function, such as bacterial recognition (17), intracellular signaling (18), and antigen binding and presentation (19).…”
mentioning
confidence: 99%